ON THE SELECTION OF DRUGS DOSAGE REGIMEN - E. N. Bochanova (Рациональная фармакотерапия в кардиологии)
A complex system of hemostasis regulation, insufficient data on drugs pharmacokinetics, multiple factors effecting treatment, including patient’s adherence to therapy, that can lead to the need for the dosage regimen specification are presented.